Mechanotransduction: from the cell surface to the nucleus via RhoA. (1st July 2019) - Burridge, Keith; Monaghan-Benson, Elizabeth; Graham, David M.
Abstract : Cells respond and adapt to their physical environments and to the mechanical forces that they experience. The translation of physical forces into biochemical signalling pathways is known as mechanotransduction. In this review, we focus on two aspects of mechanotransduction. First, we consider how forces exerted on cell adhesion molecules at the cell surface regulate the RhoA signalling pathway by controlling the activities of guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs). In the second part of the review, we discuss how the nucleus contributes to mechanotransduction as a physical structure connected to the cytoskeleton. We focus on recent studies that have either severed the connections between the nucleus and the cytoskeleton, or that have entirely removed the nucleus from cells. These actions reduce the levels of active RhoA, thereby altering the mechanical properties of cells and decreasing their ability to generate tension and respond to external mechanical forces. This article is part of a discussion meeting issue 'Forces in cancer: interdisciplinary approaches in tumour mechanobiology'.